Nicolai Møller. En næsten glemt filosof - Glebe-Møller, Jens (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
The article presents the Norwegian born (1777) philosopher Nicolai Møller, a cousin of Poul Martin Møller, Søren Kierkegaard’s much admired teacher. It traces Nicolai Møller’s career from his early days as a graduate in law in Copenhagen through his “Wanderjahre” with Henrich Steffens in Germany, where both studied at the famous Mining Academy in Freiberg and met with a number of Romantic philosophers and poets in Jena and elsewhere. Nicolai Møller became befriended with Hegel, but after his conversion to the Catholic faith, he later critized the Protestant philosopher Hegel in harsh words. Already as a law student Møller had become interested in philosophy and theology and while in Germany and later Austria he had various odd jobs but he also wrote a number of articles and books, which finally led to his being appointed as “professeur honoraire à la faculté de philosophie et lettres“ at the Catholic university of Louvain in 1835. Here he taught ancient philosophy and continued to publish articles and books, now mostly in French, until his death in 1862. One of his books, Speculative Darstellung des Christenthums, was published anonymously in Leipzig in 1819 and was in Søren Kierkegaard’s library. It is cited in one of Kierkegaard’s papers, seemingly without him knowing who the author was. But why did Kierkegaard emphatically write: “The work itself I own”?